2019
DOI: 10.1111/joor.12756
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported effect of oral rehabilitation

Abstract: Summary Objectives To quantify the patient‐reported effect of oral rehabilitation and investigate aspects associated with this. Methods The patient‐reported effect in participants treated with fixed dental prosthesis (FDP; n = 72) or removable dental prosthesis (RDP; n = 58) was measured using the Oral Health Impact Profile 14 (OHIP‐14) and global oral ratings (GOR) of aesthetics, chewing and comfort before and after treatment and global transition judgements (GTJ) of aesthetics, chewing and comfort after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…In contrast, the improvement of the OHRQoL with new removable dental prostheses in patients who had no prosthetic restoration before or new removable dental prostheses that probably have a better fit seem obvious. As in the present study, the prosthetic treatment with fixed restorations showed an improvement in OHRQoL in the scientific literature and data from other studies analyzing single-tooth restorations or multiple-unit fixed dental prostheses [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, the improvement of the OHRQoL with new removable dental prostheses in patients who had no prosthetic restoration before or new removable dental prostheses that probably have a better fit seem obvious. As in the present study, the prosthetic treatment with fixed restorations showed an improvement in OHRQoL in the scientific literature and data from other studies analyzing single-tooth restorations or multiple-unit fixed dental prostheses [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
“…The OHIP was further originally developed in patients with great tooth loss and removable prosthesis and thus might not be sensitive enough to capture the impairment of small tooth loss and subsequent effect of their replacement, independent of the length of the questionnaire. Using additional methods to capture the patient‐reported effect have also shown to yield different outcomes of prosthetic treatments . Also, we did not take response shift into account in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used OHIP-14 in Denmark. The majority [ 22 24 ] used the original English OHIP-14, whereas one study [ 25 ] reported using a translated Danish version (with no reference provided) and another study [ 26 ] reported the translation of the OHIP-49 into Danish, but without following the guidelines for translation and cross-cultural adaptation of questionnaires [ 27 ]. In the literature, there is neither a published nor a validated Danish version.…”
Section: Introductionmentioning
confidence: 99%